1992
DOI: 10.1007/bf01888507
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic liver disease with obstructive jaundice: Treatment with ultrasound-guided cyst aspiration

Abstract: A 59-year-old woman with polycystic liver (PCLD) and kidney disease (PCKD) presented with jaundice, fever, and abdominal pain. A computered tomographic (CT) scan performed immediately after an endoscopic retrograde cholangiopancreatogram (ERCP) clearly demonstrated a hepatic cyst obstructing the biliary system. The cyst was then aspirated under ultrasound guidance with complete relief of obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This is used mainly to mitigate acute complaints, as the rate of complications is high, and there is a high probability of recurrence of the cysts [3,6,9,10,11,12,13]. A number of authors suggest the sclerotization of liver cysts with ethoxysclerol or with absolute alcohol, while others report favorable experience with drainage [14,15,16] However, El Mouaaouy et al [15] observed a 6% rate of complications, including very grave ones. No complications were seen in our patients following puncture and sclerotizing treatment, but the high rate of recurrence does not indicate any advantage of this procedure.…”
Section: Discussionmentioning
confidence: 96%
“…This is used mainly to mitigate acute complaints, as the rate of complications is high, and there is a high probability of recurrence of the cysts [3,6,9,10,11,12,13]. A number of authors suggest the sclerotization of liver cysts with ethoxysclerol or with absolute alcohol, while others report favorable experience with drainage [14,15,16] However, El Mouaaouy et al [15] observed a 6% rate of complications, including very grave ones. No complications were seen in our patients following puncture and sclerotizing treatment, but the high rate of recurrence does not indicate any advantage of this procedure.…”
Section: Discussionmentioning
confidence: 96%
“…Body mass index, genotype, and baseline height-adjusted total kidney volume were not associated with the growth rate of height-adjusted liver cystic volume or height-adjusted liver volume. According to the height-adjusted liver cystic volume growth rate, patients were classified into five classes (number of women, men in each class): A (24, six); B (44, 13); C (43, 48); D (28,17); and E (13, nine).…”
Section: Resultsmentioning
confidence: 99%
“…Third, although the Mayo imaging classification model was found to be a strong predictor of subsequent eGFR decrease, our proposed polycystic liver disease imaging classification lacks proven clinical correlations. However, massive polycystic livers are a significant clinical problem for many patients due to pain and mass effects (1 7,9,11,12,15,16,28 33). Further, a previous cross-sectional study of HALT PKD demonstrated a positive correlation between increases in htLV and reductions in quality of life (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, compression of the biliary tree may be associated with the development of jaundice in these patients. 124,[128][129][130] Liver failure is rarely observed and usually associated with a very advanced disease stage. 110,116 PLD can develop in both sexes, but women usually have a more severe hepatic phenotype, especially those with a history of multiple pregnancies and prolonged exposure to exogenous estrogen.…”
Section: Clinical Presentationmentioning
confidence: 99%